Innovative Approach to Education in the System of Higher Education in Uzbekistan - Daminova Nilufar Raxmatullayevna; Qodirova Dilnoza Mamadiyorovna; Daminova Mashhura Zafar qizi; Niyozova Shoira Toirovna (Research Parks Publishing LLC, 2021)
The article analyzes the features of the innovative model of higher education. Attention is drawn to the directions of activities of higher education in the innovation process. It is shown that innovations in education are a necessity of time. The main indicator of innovation is a progressive beginning in the development of the higher education in comparison with the established traditions and mass practice. Therefore, innovation in the education system are associated with changes in objectives, content, methods and technologies, forms of organization and management system; in the styles of teaching and organizing educational process; the system of monitoring and evaluation of the level of education; training and methodological support; the curriculum and programs; a funding system.